PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION - Adi Irawan Setiyanto; Selvi Nurul Hidayati (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2017)
Turnover is one of the problem can’t be avoided all the companies due to those are being affect to company expenses such involve for hiring new manpower and wasting time for . Based on the problem is being faced , The researcher is initiatively to develop a research on previously within three great methods , they are : work satisfaction , organization's commitment and intensity of turnover which is use 162 questioners . The datas have been received from the several people will be analyzed using SPSS statistic measurement. The result show that work satisfaction did not significantly affect to turnover intention .But, organization commitment gives a big deal for turnover intention. So, based on the researching we could make a conclusion for turnover intention was affected how much the company put an effort for the commitment in organization. However the company should keep in maintenance of the commitment in organization and make continuous improvement.